Perlindungan Hukum Bagi Tenaga Kerja Atas Pemutusan Hubungan Kerja Pada Waktu Pandemi Covid-19 - Siti Afiyah; H. M. Afif Hasbullah; Mufarikhatin Ainiah (Indonesian Journal of Criminal Law, 2021)
The Research objective to analyze the legal protection for workers for termination of employment during the covid-19 pandemic according to law number 11 of 2020 concerning job creation. The research method uses a normative juridical approach. The results of the study show that legal protection for workers/labourers is related to their rights in the form of wages, severance pay, service award money, compensation for rights, which have been stipulated in Article 156 of Law Number 11 of 2020 concerning job creation, welfare of workers/labourers. such as the fulfillment of physical and spiritual needs and/or needs both inside and outside the working relationship which can directly and indirectly enhance work productivity in a safe and healthy environment for workers/laborers whose employment relationship is terminated as written in Article 1 number 30 Law Number 13 of 2003 concerning Manpower. Tujuan Penelitian menganalisis perlindungan hukum bagi tenaga kerja atas pemutusan hubungan kerja pada waktu pandemi covid-19 menurut undang undang nomor 11 tahun 2020 tentang cipta kerja. Metode penelitian menggunakan pendekatan yuridis normatih. Hasil penelitian bahwa Perlindungan hukum bagi pekerja/buruh terkait hak-hak berupa upah, uang pesangon, uang penghargaan masa kerja, uang penggantian hak, yang telah di tetapkan pada Pasal 156 Undang-Undang Nomor 11 Tahun 2020 tentang Cipta kerja, kesejahteraan pekerja/buruh seperti pemenuhan kebutuhan dan/atau keperluan yang bersifat jasmaniah dan rohaniyah baik didalam dan juga luar hubungan kerja yang secara langusung dan tidak langsung dapat mempertinggi produktivitas kerja dalam lingkungan yangaman dan sehat bagi pekerja/buruh yang di putuskan hubungan kerjanya yang ditulis dalam pasal 1 angka 30 Undang-Undang Nomor 13 Tahun 2003 tentang ketenagakerjaan.